A common sense of property?. Issue 1 (2nd January 2016) - Cockburn, Patrick J. L.
Abstract : 'Progressive' accounts of property developed in recent legal scholarship have attempted to shift focus from rights to exclude, often regarded as the 'core' of the idea and institution, towards focus on a plurality of human values served by property law. Like Thomas Grey's famous thesis about the 'disintegration of property' this raises the question of what might be called 'property perspectivism': does property looks different from different points in the social fabric? What is involved in the claim to 'know property'? To understand the diversity of property arguments within legal scholarship and across the human sciences it is important to trace the implicit knowledge claims that accompany the explicit normative arguments, paying specific attention to the 'exemplars' that underpin lines of argument, and the 'sources of property knowledge' that are drawn upon. This paper draws on and reworks W. B. Gallie's classic discussion of 'essentially contested concepts' in order to show that debates about property are as much about defining analytic starting-points as they are about reaching normative conclusions. After outlining major fault-lines in contemporary legal theorizing about property the analysis focuses in on the work of Gregory Alexander and his critics, and concludes by placing this within the even broader perspective provided by contrasting forms of property scholarship from outside of legal studies.